2009
DOI: 10.1002/cyto.a.20708
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of CHO AL mutant expression after treatment with γ radiation, EMS, and asbestos

Abstract: The flow cytometry mutation assay (FCMA) uses hybrid CHO A L cells to measure mutations of the cd59 gene located on human chromosome 11 by the absence of fluorochrome-conjugated antibody binding to the CD59 surface antigen. Mutant expression peaks between 6 and 12 days, then decreases to a stable plateau, instead of a constant mutant fraction obtained by clonogenic assays. To evaluate this variable mutant expression time, cells were treated with radiation, EMS or asbestos and cell proliferation and survival we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This discrepancy may have several explanations; first, radiation causes large deletions which are of no consequence when they occur along chromosome 11, which for the most part is not essential for survival, while large deletions of pigA on the X chromosome would often be lethal. Second, we have reported that CD59 − cells that are likely GPI mutants increase from a small fraction to the majority of total CD59 − cells measured with the FCMA over several weeks [3]. This increase could be caused by the importance of GPI linkage in the cell membrane for proper cell death signaling [24,25] allowing GPI mutants that would normally die to propagate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discrepancy may have several explanations; first, radiation causes large deletions which are of no consequence when they occur along chromosome 11, which for the most part is not essential for survival, while large deletions of pigA on the X chromosome would often be lethal. Second, we have reported that CD59 − cells that are likely GPI mutants increase from a small fraction to the majority of total CD59 − cells measured with the FCMA over several weeks [3]. This increase could be caused by the importance of GPI linkage in the cell membrane for proper cell death signaling [24,25] allowing GPI mutants that would normally die to propagate.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously characterized the flow cytometry mutation assay (FCMA) as a sensitive and rapid method of measuring the genotoxicity of known and unknown chemical and physical agents [13]. The FCMA uses the CHO A L cell line that has an incorporated human chromosome 11 as well as the entire hamster genome.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported previously that the survival of cells sorted from the mutant regions on the peak day of mutant expression after treatment with EMS or γ radiation was lower than that of cells sorted from the CD59 + peak of the same population (23). The surviving fraction of cells from the CD59 − region (0.69 ± 0.07) was significantly less than those from the treated positive peak (0.83 ± 0.05) ( P < 0.02).…”
Section: Resultsmentioning
confidence: 94%
“…We showed previously that the return to control survival of treated cells is an indicator of the peak day of mutant expression after treatment with genotoxic agents (23). Cells were sorted from hypoxia-treated and control populations from days 2–12 after treatment and grown into colonies for survival analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation